PEMBUATAN GAME FIGHTING “BRAWLMANIA” - Stanley, Tarsisius; Pragantha, Jeanny; Haris, Darius Andana (Faculty of Information Technology, Universitas Tarumanagara, 2019)
Brawlmania is a fighting game. The game is developed in C# programming language and uses Unity game engine. The game is a 2D game. The background of the game is the Universitas Tarumanagara. This game provides three modes of playing, which are arcade, versus, and practice modes. The arcade mode is where the players fight using 8 characters controlled by AI in a sequence. The player can achieve higher score playing in this mode, which can then be compared to another player's. Ten players with the highest score will be registered on the high score list. The versus mode is where one player fights against another character controlled by either AI or another human player. In the versus mode, they can choose several settings, such as the battle ground, battle rounds, and time limit for each rounds. The practice mode is where the human player can practice using a character fighting against a dummy. There are eight playable characters. Each characters represents a faculty in Universitas Tarumanagara which has their own unique combos. The testing is conducted by 30 resondents. The result shows that the provided gameplay and game features is exciting and interesting for a fighting game. Game Brawlmania adalah sebuah fighting game. Game ini dibuat menggunakan bahasa pemrograman C# dalam game engine Unity. Game memiliki tampilan dua dimensi. Situasi dalam game meminjam latar dari Universitas Tarumanagara. Game ini menyediakan tiga mode permainan yaitu Arcade, Versus, dan Practice. Arcade adalah tempat player bertarung dengan 8 karakter yang dikendalikan AI secara beruntun. Player juga memperoleh score ketika memainkan mode tersebut yang dapat dibandingkan dengan score player lain. Sepuluh player dengan score tertinggi akan terdaftar dalam menu High Score. Versus adalah tempat player bertarung dengan karakter yang dikendalikan oleh AI atau player lain. Di dalam mode Versus, dapat dilakukan pengaturan seperti tempat arena bertanding, banyaknya ronde bertarung, dan batas waktu untuk tiap ronde. Practice adalah tempat player berlatih menggunakan karakter melawan dummy. Ada delapan karakter yang dapat dimainkan. Setiap karakter mewakili fakultas yang ada di Universitas Tarumanagara dan memiliki gerakan kombo dan keunikan sendiri. Pengujian pada game dilakukan oleh 30 responden. Hasil pengujian menunjukkan bahwa gameplay dan fitur yang disediakan sudah cukup menarik untuk sebuah fighting game.